BODY IMAGE ASSESSMENT AND ATTITUDES TOWARDS EATING DISORDERS IN UNIVERSITY STUDENTS AT THE EVANGELICAL UNIVERSITY OF GOIÁS (CIPEEX, 2025)
Eating disorders (EDs) are characterized by constant fear of weight gain, excessive concern with body shape, and changes in eating patterns. Given the increased incidence of EDs and their repercussions, it is essential to develop research that establishes correlations between their development and etiology. The present study aims to evaluate the relationship between sociodemographic profile and the degree of dissatisfaction with body image, as well as attitudes related to EDs in university students enrolled in Pharmacy, Medicine, Nutrition, and Aesthetics and Cosmetics Technology courses at the Evangelical University of Goiás. This is a descriptive, analytical, cross-sectional study with a quantitative approach. Data were collected through validated questionnaires, such as the Eating Attitudes Test (EAT-26) and the Body Shape Questionnaire (BSQ), as well as sociodemographic and anthropometric questionnaires. This study was submitted to and approved by the Research Ethics Committee (CEP/UniEVANGÉLICA), in accordance with Resolution 466/2012 of the National Health Council (CNS). Statistical analysis of the BSQ and EAT-26 data revealed a significant association between the course (p < 0.001) and gender (p < 0.001), especially among female students in the Aesthetics and Cosmetics Technology course, who reported greater body dissatisfaction and increased risk for eating disorders. These findings highlight the importance of identifying attitudes related to eating disorders among university students, understanding the prevalence and impact of these conditions, and promoting interventions aimed at improving the health of the study population.
Keywords: Body dissatisfaction; Eating disorders; University students; Sociodemographic factors.